Composing and Shaping of Web Text - Botirov Muzaffarjon Mansurovich (International Journal on Integrated Education, 2022)
Designing and creation of a Web page is like production of a book. It’s a creative work, involving many a task like writing, maintenance of style, designing, adding of pictures and graphs, and shaping up the appearance. In the same line, the Web page offers scope for conveying and communicating information using a variety of options including text, graphics, photos, video, sound, animation, and link to other sites. In this article, we shall, however, confine to discussion on composing and shaping of Web text.